Pancreatico‑pleural Fistula: Case Series - Manoj Munirathinam; Pugazhendhi Thangavelu; Ratnakar Kini (Journal of Digestive Endoscopy, 2018)
Pancreatico‑pleural fistula is a rare but serious complication of acute and chronic pancreatitis. The pleural effusion caused by pancreatico‑pleural fistula is usually massive and recurrent. It is predominately left‑sided but right‑sided and bilateral effusion does occur. We report four cases of pancreatico‑pleural fistula admitted to our hospital. Their clinical presentation and management aspects are discussed. Two patients were managed by pancreatic endotherapy and two patients were managed conservatively. All four patients improved symptomatically and were discharged and are on regular follow‑up. Most of these patients would be evaluated for their breathlessness and pleural effusion delaying the diagnosis of pancreatic pathology and management. Hence, earlier recognition and prompt treatment would help the patients to recover from their illnesses. Pancreatic pleural fistula diagnosis requires a high index of suspicion in patients presenting with chest symptoms or pleural effusion. Extremely high pleural fluid amylase levels are usual but not universally present. A chest X‑ray, pleural fluid analysis, and abdominal imaging (magnetic resonance cholangiopancreatography/magnetic resonance imaging abdomen more useful than contrast‑enhanced computed tomography abdomen) would clinch the diagnosis. Endoscopic retrograde cholangiopancreatography with stent or sphincterotomy should be considered when pancreatic duct (PD) reveals a stricture or when medical management fails in patients with dilated or irregular PD. Surgical intervention may be indicated in patients with complete disruption of PD or multiple strictures.